1993
DOI: 10.1007/bf01623169
|View full text |Cite
|
Sign up to set email alerts
|

Loss of bone mass in patients with Klinefelter's syndrome despite sufficient testosterone replacement

Abstract: To determine whether testosterone replacement therapy reverses the detrimental effects of hypogonadism on bone density, we measured the total body, lumbar spine and proximal femur bone mineral density (BMD) by dual-energy X-ray absorptiometry in 14 patients with Klinefelter's syndrome on long-term testosterone replacement therapy and compared the results with 14 age- and sex-matched normal controls. Seven of the patients were receiving oral testosterone undecanoate thrice daily (240 mg/day) and the others were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 18 publications
2
31
0
Order By: Relevance
“…In both situations, although testosterone was synthesised and the androgen receptor (AR) unaffected, there was abnormal skeletal development and marked osteopenia. Furthermore, although there are reports that testosterone treatment improved bone mineral density in hypogonadal men (Behre et al 1997), osteoporotic patients with Klinefelter's disease did not respond to this treatment (Wong et al 1993), nor was it effective in treating males with aromatase deficiency (Carani et al 1997). They, however, responded to oestrogen.…”
Section: Importance Of Oestrogens For Maintaining Bone In Men and Womenmentioning
confidence: 99%
“…In both situations, although testosterone was synthesised and the androgen receptor (AR) unaffected, there was abnormal skeletal development and marked osteopenia. Furthermore, although there are reports that testosterone treatment improved bone mineral density in hypogonadal men (Behre et al 1997), osteoporotic patients with Klinefelter's disease did not respond to this treatment (Wong et al 1993), nor was it effective in treating males with aromatase deficiency (Carani et al 1997). They, however, responded to oestrogen.…”
Section: Importance Of Oestrogens For Maintaining Bone In Men and Womenmentioning
confidence: 99%
“…Our results on the age dependency of the efficacy of androgen substitution on BMD underline the necessity to commence androgen substitution in hypogonadism as early as possible, albeit in adolescence achieving an appropriate final height must be kept in mind. Nevertheless, the results of our study indicate that delayed onset of substitution might not be able to normalize BMD any more, even when androgens are given over extended periods of time [8, 23, 24]. …”
Section: Discussionmentioning
confidence: 88%
“…Despite the widespread assumption that testosterone substitution increases the bone mineral density (BMD) in male hypogonadism, evidence is based on very small patient numbers [5, 6, 7], not unanimously [8], and a recent review concluded that an anabolic effect on bone is not obvious from the available data [9]. Furthermore, so far no study exists investigating the effects of different modes of androgen substitution on the BMD.…”
Section: Introductionmentioning
confidence: 99%
“…These considerations suggest that suboptimal testosterone replacement dosage may be an overlooked determinant of previously reported inadequate bone density response to testosterone rather than unexplained independent bone effects of the underlying disorders causing hypogonadism (14,46). Recognizing the importance of sustaining adequate testosterone treatment over prolonged periods may also lead to reconsideration of claims that bone deficits occurring in adolescence (prior to acquisition of peak bone mass (47)) may not be correctable in the light of more effective treatment.…”
Section: Discussionmentioning
confidence: 99%